87=3(-3x+8)

Simple and best practice solution for 87=3(-3x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 87=3(-3x+8) equation:


Simplifying
87 = 3(-3x + 8)

Reorder the terms:
87 = 3(8 + -3x)
87 = (8 * 3 + -3x * 3)
87 = (24 + -9x)

Solving
87 = 24 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
87 + 9x = 24 + -9x + 9x

Combine like terms: -9x + 9x = 0
87 + 9x = 24 + 0
87 + 9x = 24

Add '-87' to each side of the equation.
87 + -87 + 9x = 24 + -87

Combine like terms: 87 + -87 = 0
0 + 9x = 24 + -87
9x = 24 + -87

Combine like terms: 24 + -87 = -63
9x = -63

Divide each side by '9'.
x = -7

Simplifying
x = -7

See similar equations:

| 4x(x+4)=9 | | 3n+5-4n=-22 | | 6x-21=33+10x | | 30x+65y=5840 | | -2(7k+9)=25 | | =95-2 | | 2(3x-10)=1 | | 4x+12x=-2254 | | -8(3+9a)=-20 | | 6(3x-10)=46 | | 5(3x-10)=46 | | 4(3x-10)=46 | | 3(3x-10)=46 | | 1(3x-10)=46 | | 12x-25=-63+7x | | 3(-2x+5)=12-4x | | -8x+4=-2(4x-2) | | -y=12-6x | | -20=2y-4 | | monkey+hat=toad | | 6x-y=12fory | | 8x+4=-2(4x-2) | | G=(x+y)(ax+bxy) | | ln(4-x)+ln(2)=2ln(x) | | G=ax(x+y)+bxy(x+y) | | 5w+10=5w+10 | | -19x-34=56+x | | 25-5x=4x-20 | | 16x-19=120+6x | | 10x+8x+12x+4x+9x+3-12-9+2-3=360 | | 3x+4=9+x | | 2x+9=3x-20 |

Equations solver categories